Uji Produktivitas Calon Bibit G4 FP005 Jamur Merang (Volvariella volvaceae) Faperta UNSIKA Menggunakan Media Jerami dengan Metode Pemanenan Konvensional dan Mesin Combine Harvester - Ghufron Asno Ifanda; Bastaman Syah; Ani Lestari (UNIVERSITAS LABUHANBATU, 2023)
Mushrooms are one of the agricultural commodities that have good prospects for development and cultivation. The purpose of this study is to compare the characteristics of the mangrove fungus (Volvariella volvaceae) in the straw growing medium of conventional harvesting methods and Combine Harvester. The research was conducted at the Merang mushroom barn in Pasir Buah Hamlet, Pasimulya Village, Majalaya District, Karawang Regency. In March–April 2023. The research method used the Single-factor Randomized Design (RAK) with 3 repeats. There are 12 treatments: A (Gebot 100%), B (Combine 100%), C (Trasher 100%), D (Gebot 50%+Combine 50%), E (Gebot 50%+Trasher 50%), F (Combine 50%+Trasher 50%), G (Gebot 75%+Jobotine 75%), F (Combine 50%+Tras 50%), G (Gebot 75%+25%), G (G) and 75%). The effect of treatment is analyzed by variety analysis and if the F test is 5% significant, then to find out which treatment is best to proceed with the DMRT (Duncan Multiple Range Test) at 5%. The research results show that there is no real effect of some straw media using machines on Unsika's G4 Faperta isolates. The treatment of Gebot 75% + Combine 25% gave the highest yield on a single-heel conversion mushroom weight of 182.47 kg, and the average harvest intensity of a single growing season for 14.67 days. The 50% + 50% Gebot treatment gave the best value at the time of pinhead appearance of 6.0 days and a fruit body weight of 12.71g. The Gebot 75% + Combine 25% treatment gave the best results at 6.18cm in length and 4.99cm in fruit body diameter while the Gebot 75% + Trasher 25% treatment gave the best value at a per tray weight of 54.99g. Keywords:G4 Faperta Isolate, Straw Mushroom, Straw Harvesting Method